Airships in International Affairs 1890 - 1940 - Duggan, J. author. aut Link
XIX, 275 p.
Keywords: This book analyses the unique psychological appeal of the airship worldwide and shows how this appeal was exploited for ulterior political purposes. They were used by Count Zeppelin to advance German militarism, American Admiral Moffett to fight US Army aviation ambitions, British Lord Thomson to foster Socialism and strengthen Empire ties, Mussolini to promote Italian Fascism, Stalin to foster world Communism, and Hitler to promote Nazi ideology. As airships roamed worldwide, so they carried these political influences with them.